Determination of Genetic Polymorphism Among Soybean (Glycine max. L. Merrill) Cultivars Developed in Recent Years through RAPD Markers - Mine PAKYÜREK (International Journal of Secondary Metabolite, 2015)
Genotype or cultivar identification is the first step to ensure plant breeder’s rights. If registered cultivars or germplasms were not distinguished by any mechanism, then seed production or novel varieties could not be controlled. The RAPD markers are chosen to distinguish seven soybean ( Glycine max. L. Merrill ) cultivars from each other and to assign the polymorphisms among of them in this study. Eight primers were used and DNA fingerprinting of all cultivars were determined with that primers. According to that fingerprinting all cultivars were distingusihed from each other in DNA banding pattern. Using these markers results, similarity index in between soybean cultivars were calculated. Dwight and Maverick were the most similar cultivars ( These two cultivars were similar at 0,70 point to each other. ) In addition that Maverick and Defiance cultivars have shown the highest polymorphism rate ( These two cultivars were similar at 0,39 point each other. ).